Reimagining psychosis prevention: responding to the accessibility issues of At-Risk Mental State (ARMS) services through a selective public health approach - Luke Brown; Siân Lowri Griffiths (BJPsych Bulletin)
At-Risk Mental State (ARMS) services aim to prevent the onset of first-episode psychosis (FEP) in those with specific clinical or genetic risk markers. In England, ARMS services are currently expanding, but the accessibility of this preventative approach remains questionable, especially for a subgroup of FEP patients and those from specific ethnic minority communities. This commentary outlines the key debates about why a complimentary approach to psychosis prevention is necessary, and gives details for an innovative public health strategy, drawing on existing research and health prevention theory.